The early bird catches the worm: The impact of first-mover advantage on long-term elite team sport success - Frank Daumann; Florian Follert; Daniel Hamacher; Lasse Plöhn (Managerial and Decision Economics, 2022)
The research on success factors in elite sport focuses primarily on the one hand to sport in its entirety and on the other hand to the prediction of success in individual sporting events, especially in soccer. In this paper, we investigate the existence of a first-mover advantage for national team sports, which has a long-term impact on a nation's success in a sport. To this end, we hand-collected data for soccer and rugby and analyzed our sample concerning a first-mover advantage. To do this, we examined the relationship between the date of establishment of each national sports association and later success as measured by the country's world ranking. We check for the essential macro determinants such as GDP per capita and population. Our study shows empirical evidence that the first-mover advantage has a stronger effect on the success of a state in a team sport than the macro factors mentioned. In this way, we complement previous research on team sports by considering a hitherto neglected effect, a long-term perspective and by including rugby.
Keywords: 650